2020
DOI: 10.1097/prs.0000000000006560
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid for the Plastic and Reconstructive Surgeon

Abstract: Summary: Medicaid is a complex federally and state funded health insurance program in the United States that insures an estimated 76 million individuals, approximately 20 percent of the U.S. population. Many physicians may not receive formal training or education to help understand the complexities of Medicaid. Plastic surgeons, residents, and advanced practice practitioners benefit from a basic understanding of Medicaid, eligibility requirements, reimbursement methods, and upcoming healthcare tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A list of common plastic surgery procedures and their associated relative value units are shown in Table 1. 10,11 Relative value units are then converted into a monetary value using a "conversion factor" to a fee schedule expressed in dollars. Although relative value units have been highly criticized, they remain the most common measure of surgeon productivity in the United States.…”
Section: Productivity-based Compensation Models: Relative Value Unitsmentioning
confidence: 99%
“…A list of common plastic surgery procedures and their associated relative value units are shown in Table 1. 10,11 Relative value units are then converted into a monetary value using a "conversion factor" to a fee schedule expressed in dollars. Although relative value units have been highly criticized, they remain the most common measure of surgeon productivity in the United States.…”
Section: Productivity-based Compensation Models: Relative Value Unitsmentioning
confidence: 99%
“…With Congress periodically weighing changes that impact plastic surgeons, a primer on each topic by Firouzbakht et al is a helpful guide. 20,21 Nearly half of plastic surgeons report that 10 to 30 percent of their practice is made up of patients covered by Medicare. Whether Medicare reimburses for plastic surgery procedures depends on the "medical necessity" of the procedure, and clinical criteria and required documentation are strict.…”
Section: Medicare and Medicaidmentioning
confidence: 99%
“…For a plastic surgeon, knowing procedure coverage criteria for the state in which one practices is essential to serve the growing subpopulation of patients. 21…”
Section: Medicare and Medicaidmentioning
confidence: 99%
“…The state of Maryland serves as an interesting case study of reconstructive surgery utilization by underserved populations (Medicaid patients) 4 . While Maryland expanded Medicaid coverage under the Affordable Care Act (ACA) in 2014, it also implemented a statewide policy mandating global budgets for hospitals that same year through its All-Payer Model (APM) 5–7 . The APM was designed to limit healthcare spending by disincentivizing low-value care (ie, readmissions) 8 …”
mentioning
confidence: 99%
“…4 While Maryland expanded Medicaid coverage under the Affordable Care Act (ACA) in 2014, it also implemented a statewide policy mandating global budgets for hospitals that same year through its All-Payer Model (APM). [5][6][7] The APM was designed to limit healthcare spending by disincentivizing low-value care (ie, readmissions). 8 Prior literature has demonstrated that the ACA broadened access to a variety of health services, including surgical procedures, for Medicaid beneficiaries.…”
mentioning
confidence: 99%